Water from heaven : the story of water from the big bang to the rise of civilization, and beyond - Kandel, Robert S. (Columbia University Press, 2003)
From where--and what--does water come? How did it become the key to life in the universe? Water from Heaven presents a state-of-the-art portrait of the science of water, recounting how the oxygen needed to form H2O originated in the nuclear reactions in the interiors of stars, asking whether microcomets may be replenishing our world's oceans, and explaining how the Moon and planets set ice-age rhythms by way of slight variations in Earth's orbit and rotation. The book then takes the measure of water today in all its states, solid and gaseous as well as liquid. How do the famous El Niño and La Niña events in the Pacific affect our weather? What clues can water provide scientists in search of evidence of climate changes of the past, and how does it complicate their predictions of future global warming? Finally, Water from Heaven deals with the role of water in the rise and fall of civilizations. As nations grapple over watershed rights and pollution controls, water is poised to supplant oil as the most contested natural resource of the new century. The vast majority of water "used" today is devoted to large-scale agriculture and though water is a renewable resource, it is not an infinite one. Already many parts of the world are running up against the limits of what is readily available. Water from Heaven is, in short, the full story of water and all its remarkable properties. It spans from water's beginnings during the formation of stars, all the way through the origin of the solar system, the evolution of life on Earth, the rise of civilization, and what will happen in the future. Dealing with the physical, chemical, biological, and.